Posterity inventing tradition from Petrarch to Gramsci - Rubini, Rocco (University of Chicago Press, 2022)
Reading a range of Italian works, Rubini considers the active transmittal of traditions through generations of writers and thinkers. Rocco Rubini studies the motives and literary forms in the making of a "tradition," not understood narrowly, as the conservative, stubborn preservation of received conventions, values, and institutions, but instead as the deliberate effort on the part of writers to transmit a reformulated past across generations. Leveraging Italian thinkers from Petrarch to Gramsci, with stops at prominent humanists in between--including Giambattista Vico, Carlo Goldoni, Francesco De Sanctis, and Benedetto Croce--Rubini gives us an innovative lens through which to view an Italian intellectual tradition that is at once premodern and modern, a legacy that does not depend on a date or a single masterpiece, but instead requires the reader to parse an expanse of writings to uncover deeper transhistorical continuities that span six hundred years. Whether reading work from the fourteenth century, or from the 1930s, Rubini elucidates the interplay of creation and the reception underlying the enactment of tradition, the practice of retrieving and conserving, and the revivification of shared themes and intentions that connect thinkers across time. Building on his award-winning book, The Other Renaissance, this will prove a valuable contribution for intellectual historians, literary scholars, and those invested in the continuing humanist legacy